Application of Whole-Genome Sequencing to an Unusual Outbreak of Invasive Group A Streptococcal Disease. (19th February 2016) - Galloway-Peña, Jessica; Clement, Meredith E.; Sharma Kuinkel, Batu K.; Ruffin, Felicia; Flores, Anthony R.; Levinson, Howard; Shelburne, Samuel A.; Moore, Zack; Fowler, Vance G.
Abstract: Whole-genome analysis was applied to investigate atypical point-source transmission of 2 invasive group A streptococcal (GAS) infections. Isolates were serotype M4, ST39, and genetically indistinguishable. Comparison with MGAS10750 revealed nonsynonymous polymorphisms in ropB and increased speB transcription. This study demonstrates the usefulness of whole-genome analyses for GAS outbreaks.